Recent applications of stimulus-responsive smart hydrogels for osteoarthritis therapy - Xu, Zhuoming; Liu, Jintao; Hu, Hanyin; Ma, Jun; Yang, Haiyang; Chen, Jiayi; Xu, Hongwei; Hu, Haodong; Luo, Huanhuan; Chen, Gang (Frontiers in Bioengineering and Biotechnology, 2025)
Osteoarthritis is one of the most common degenerative joint diseases, which seriously affects the life of middle-aged and elderly people. Traditional treatments such as surgical treatment and systemic medication, often do not achieve the expected or optimal results, which leads to severe trauma and a variety of side effects. Therefore, there is an urgent need to develop novel therapeutic options to overcome these problems. Hydrogels are widely used in biomedical tissue repairing as a platform for loading drugs, proteins and stem cells. In recent years, smart-responsive hydrogels have achieved excellent results as novel drug delivery systems in the treatment of osteoarthritis. This review focuses on the recent advances of endogenous stimuli (including enzymes, pH, reactive oxygen species and temperature, etc.) responsive hydrogels and exogenous stimuli (including light, shear, ultrasound and magnetism, etc.) responsive hydrogels in osteoarthritis treatment. Finally, the current limitations of application and future prospects of smart responsive hydrogels are summarized.